Teacher's attitudes about evaluation in the teaching process - Kolak, Ante (Array, 2012)
The introduction of the present paper is focused on terminology determinants related to evaluation in the teaching process, making a difference between the components of the evaluation through monitoring, testing, assessment, measurement and grading. When elaborating certain components, we focused on purpose, function, types and forms of evaluation in the teaching process. We considered various teaching activities related to the process of evaluation, highlighting advantages, disadvantages and possible mistakes. Our research is focused on the examination of teachers' attitudes about the evaluation process in elementary schools. The objective was to find out their attitudes related to the evaluation as a very important segment of the teaching process, as well as to identify variables that can influence the teachers' attitudes. The study was conducted on a sample of classroom teachers from Croatia (N = 1308). We used the method of questionnaires and assessment, while the instrument is a combination of questionnaires and assessment scales. Descriptive parameters were used to determine descriptive indicators, while factor analysis of common analysis was used to determine latent dimensions that underly inter-correlation particles. In order to compare the subjects by the set characteristics, one-way analysis of variance was used. Factor analysis of common factors was conducted on 17 particles that measure the evaluation of the teaching process based on content, and three factors by the Kaiser-Guttman criterion were extracted. The Kaiser-Meyer-Olkin coefficient of 0.93 confirmed the suitability of matrix correlation of the assessment scale of the teaching process for the factor analysis. Internal consistency reliability, Chronbach alpha, confirmed the high reliability of the evaluation scale. In order to confirm the hypothesis related to teachers' attitudes and certain characteristics of subjects, the conducted variance analysis showed there were statistically significant differences between the subjects as to work experience and age, while no significance was determined in other characteristics. The data processing showed that the particles in the evaluation scale were indeed reliable, therefore they could be used in further analyses and studies as a reliable measure. The differences related to certain characteristics of the subjects can determine the direction of teachers’ further professional improvement related to the evaluation process.